Translating Freedom for Post-1997 Hong Kong - Frances H. Foster (Washington University Law Quarterly, 1998)
This Article explores possible approaches China might use to define Basic Law freedoms for post-1997 Hong Kong. It focuses specifically on the People's Republic of China ("P.R.C.") interpretation of one such freedom- "freedom of the press." Part I identifies and considers six techniques recently proposed by Hong Kong, Chinese, and foreign commentators, which I call the strict literalist approach, the integrated constitution approach, the law on the books approach, the law in action approach, the liberties with Chinese characteristics approach, and the balancing approach. I argue that all six are implausible. They fail to accommodate China's two key goals for the post- 1997 era-to maintain its formal commitment to the "one country, two systems" policy and, at the same time, to preserve maximum flexibility to respond to changing needs and circumstances during Hong Kong's fifty-year transition from capitalism to socialism. Parts II and III present a new framework, drawn from U.S. scholarship on constitutional interpretation. I argue that the metaphor of "translation" best captures China's likely method of interpreting Hong Kong freedoms, including "freedom of the press." Under this translation approach, China will turn to pre-1997 Hong Kong definitions of "freedom of the press" as its base standard and then "translate" them into the new context of a Hong Kong that is now an "inalienable part" of China. As a result, Hong Kong will end up with neither a Western nor a P.R.C. system of press freedom. It will receive what China deems the "equivalent" of the "freedom of the press" it enjoyed before the handover with a few "minor" adjustments to reflect changed conditions in the post-1997 era. The Article concludes with a critical evaluation of China's role as translator of Hong Kong freedom.
Keywords: Freedom of the press – Hong Kong; Constitutional law – Hong Kong; Freedom of the press; China; Hong Kong